Essentials of investments - Bodie, Zvi; Kane, Alex 1942-; Marcus, Alan J. (New York McGraw-Hill, 2022)
"Essentials of Investments, Twelfth Edition, is intended as a textbook on investment analysis most applicable for a student's first course in investments. The chapters are written in a modular format to give instructors the flexibility to either omit certain chapters or rearrange their order. The highlights in the margins describe updates and important features in this edition"--
Includes bibliographical references and index.
Keywords: Investments